Analisis Faktor-Faktor Pembentuk Loyalitas Pelanggan Produk Outdoor pada Toko Paramount Pagar Alam - Ahmad Feriyansyah; Yadi Maryadi; Novriansyah . (LPPM Universitas Lembah Dempo, 2022)
The purpose of this study was to determine the factors that shape customer loyalty for outdoor products at Paramount Stores in Pagar Alam City. The research method used is descriptive qualitative. Primary data obtained from questionnaires distributed to 75 respondents who are consumers who buy products at the Paramount Pagar Alam store and direct interview data on the object of research. Secondary data was obtained through literature study (relevant books and literature) and agency internal data. The indicators used are obtained from this study, namely the dimensions of consumer behavior which consist of 1) Making repeat purchases on a regular basis, 2) Buying between product or service lines, 3) Referring to others, and 4) Showing immunity from the appeal of similar products from others. competitor. Based on the results of the study, it was concluded that from the 10 statements that became the research indicators, it was found that 4 statements were declared quite good, and there were 6 statements that were not good. The fact that the authors found in the field that the results of respondents' responses to the variable statement Making repeated purchases on a regular basis were responded to agree by consumers. However, there are still consumers who buy products at the Paramount Pagar Alam store, regardless of their income level, but their choice of brands other than certain clothing brands, there are still other brands that have more attractive designs.